2022
DOI: 10.1111/rec.13738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating biological properties of topsoil for post‐mining ecological restoration: different assessment methods give different results

Abstract: Salvaged native topsoil is a scarce, highly valuable resource in post-mining restoration, being the main source of organic matter and nutrients and a major repository of plant propagules and soil microbes. During the mining process, topsoil is often stockpiled, and factors such as stockpile depth, season of stripping, and storage time can adversely affect topsoil functionality. We aimed to determine if soil functionality differs between undisturbed native reference topsoils and stockpiled topsoils of various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The selected inoculant was used under the assumption that it contained live, viable beneficial microorganisms as stated. The bacterial composition of the GOGO Juice inoculant was verified using 16S rRNA sequencing following the method described in D'Agui et al. (2022) ; Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The selected inoculant was used under the assumption that it contained live, viable beneficial microorganisms as stated. The bacterial composition of the GOGO Juice inoculant was verified using 16S rRNA sequencing following the method described in D'Agui et al. (2022) ; Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Seed‐based strategies are widely used as a relatively low‐cost, large‐scale grassland restoration (D'Agui et al 2022; Gerrits et al 2023) and post‐mining sites (Dalziell et al 2022). However, seed‐based strategies often show low success for campo rupestre (Le Stradic et al 2014; Figueiredo et al 2021), as indicated by low seedling emergence, and the prevalence of invasive species in the initial years of restoration.…”
Section: The Ecology Threats and Challenges To Campo Rupestre Restora...mentioning
confidence: 99%
“…Native topsoil is a scarce, highly valuable resource in post‐mining restoration; however, handling and storage during the mining process can adversely affect its functionality. D'Agui et al (2022) report that when taken in isolation, commonly employed measures of soil microbial community composition and activity are poor indicators of soil functionality as reflected in plant growth. Customized approaches to topsoil management should be considered for individual sites to maintain soil functionality.…”
Section: Topsoil Degradationmentioning
confidence: 99%